Prosody and absolute vs. relative uses of English and Slovene adjectives - Monika Kavalir (Linguistica, 2017)
The paper explores the role prosody plays in distinguishing two types of uses of adjectival structures in English and Slovene. In both languages, adjectival structures can be used with an internal standard, yielding an absolute interpretation, or with an external standard (typically comparing the nominal referent to other members of the same category), giving rise to a relative interpretation. It is shown that, in the base degree, a focus on the adjective provides disambiguation by making it clear that the construction is an instance of absolute use. In the comparative and superlative degrees, however, structural differences in the intonation patterns of the two languages come into play in the case of analytic comparison, so that in Slovene reduction in stress signifies absolute use, but in English relatively used comparatives and superlatives can be unstressed as well.